Efficiency of taking first differences in regression analysis - note - Tillman, JA (Economic & Social Studies, 1973)
In a recent article, Geary [1972] discussed the merit of taking first differences to deal with the problems that trends in data present in regression analysis. Geary gave examples of situations where this procedure leads to highly inefficient estimates of the regression coefficients. The first difference transformation has also been suggested as an appropriate way of dealing with multicollinearity among the independent variables, for example Kane [1968, p, 280].
Keywords: Regression analysis